Effects of operational parameters on fuel gas production from DC-transferred arc plasma processing of sewage sludge - Júnior, Pedro William Paiva Moreira; de Souza Miranda, Felipe [UNESP]; Francelosi Azevedo Neto, Nilton; Essiptchouk, Alexei Mikhailovich [UNESP]; Prado, Eduardo Sant Ana Petraconi; da Cruz, Antonio Carlos; Petraconi Filho, Gilberto (Taylor & Francis, 2024)
In this work, a DC-transferred arc plasma reactor was used to investigate the influence of operating parameters on the process of gas production from sewage sludge treatment. By varying the operating temperature, feedstock feed rate and exhaust gas flow, the study aims to elucidate the physicochemical mechanisms during plasma treatment. The sewage sludge from the municipal wastewater treatment plant has an ash content of 40.5%, consisting mainly of Si, Al, Fe and Ca (>75%), and a complex organic fraction containing carbonyls, amines and amides. At a constant mass of feedstock (without feed rate), the gas produced by the plasma treatment was obtained with a maximum syngas fraction of 86% and a heating value of 10,000 kJ/m3, while the process operated at a constant sludge feed rate of 300 g/min increased the volumetric fraction of the syngas to 95% and the heating value to 12,000 kJ/m3.
Keywords: DC-transferred arc plasma; energy recovery; fuel gas; Sewage sludge; syngas; waste management